The time between intention and action affects the experience of action - Vinding, Mikkel C.; Jensen, Mads; Overgaard, Morten (Frontiers in Human Neuroscience, 2015)
We present a study investigating how the delay between the intention to act and the following action, influenced the experience of action. In experiments investigating sense of agency and experience of action, the contrast is most often between voluntary and involuntary actions. It is rarely asked whether different types of intentions influence the experience of action differently. To investigate this we distinguished between proximal intentions (i.e. intentions for immediate actions) and delayed intentions (i.e. intentions with a temporal delay between intention and action). The distinction was implemented in an intentional binding paradigm, by varying the delay between the time where participants formed the intention to act and the time at which they performed the action. The results showed that delayed intentions were followed by a stronger binding effect for the tone following the action compared to proximal intentions. The actions were reported to have occurred earlier for delayed intentions than for proximal intentions. This effect was independent of the binding effect usually found in intentional binding experiments. This suggests that two perceptual shifts occurred in the contrast between delayed intentions and proximal intentions: The first being the binding effect, the second a general shift in the perceived time of action. Neither the stronger binding effect for tone, nor the earlier reports of action, differed across delays for delayed intentions. The results imply that delayed intentions and proximal intentions have a different impact on the experience of action.